Mechanism of exogenous enzymes participation in the regulation of digestion and metabolism in model chickens - Vertiprakhov, Vladimir; Dashieva, Bayarma S.; Grigoriev, Alexei M.; Ashikhmina, Veronika D. (Frontiers in Veterinary Science, 2025)
Experiments were performed on fistulas with duodenal cannula, which can reflect the function of the pancreas and are a model for studying digestion and metabolism when using biologically active additives. The aim of this work is to study the effect of different doses of enzyme preparation prepared from pig pancreas tissue on duodenal enzyme activity, calcium phosphorus, blood biochemical status and productivity in laying hens using fistula technology. The enzyme preparation prepared from pig pancreatic gland tissue was standardized for trypsin activity, which was 187 units/g. The results showed that a dose of 0.01% of the enzyme preparation from the feed weight stimulated metabolism and influenced productive metabolism, increasing egg production by 25.0% compared to the control group, increasing the dose of the preparation led to an increase in trypsin activity in the duodenum, but critically influenced egg formation, reducing its mass by 5.8% and increasing egg laying capacity by 12.5% against the control. Consequently, the use of enzymes should be controlled from the side of mineral metabolism, which can be disturbed at high doses of the drug.